Explaining the Belated Emergence of Social Protest in Ireland Between 2009 and 2014 - Layte, Richard; Landy, David (SSISI, 2017)
In the summer of 2009, Ireland was the first European country to officially enter recession following the fiscal crisis which had enveloped the international banking system following the bankruptcy of Lehman Brothers in September 2008. Unemployment, which had been increasing for over a year by that point from a low of under 4.6% in early 2007 went on to peak at over 15% in 2012. This contributed, in part, to the widespread fall in income (the median household income fell by 12.7% between 2009 and 2013) and increase in household deprivation experienced in Ireland where the household deprivation rate increased from 17% in 2009 to over 30% by 2013. The squeeze on household incomes was accompanied by severe cuts in public services across areas such as health, education and social services, all of which were more likely to be visited upon more vulnerable members of Irish society.
read before the Society, 20 April 2017; Symposium 2016-2017: Globalisation, Inequality and the Rise of Populism
Keywords: 314.15